New data on conodonts and ostracods of the Katkoyeh Formation (Lower–Upper Ordovician) at the Banestan Section of East-Central Iran: biostratigraphical and palaeobiogeographical significance - Poursalehi, Farzad (2022)
Ordovician marine sedimentary sequences occur in several widely separated structural blocks in Iran, along the northern margin of Gondwana. In northern Kerman Province, the Ordovician sedimentary interval is known as the Katkoyeh Formation, which encompasses ~ 70–300 m of siliciclastic rocks with scarce carbonate and thick pyroclastic beds in its upper part. Previous studies provided several ages for the Katkoyeh Formation, puzzled by the limited number of palaeontological studies, mostly based on spot samples, the presence of regional important stratigraphic gaps, and the inherent structural complexity of the area. In order to adjust the depositional time of the Katkoyeh Formation, a systematic sampling for microfossils was conducted in the Banestan Section, located about 12 km northwest of the city of Zarand, in the vicinity of the Banestan village. Based on the occurrence of important biostratigraphic species, we recorded three conodont intervals in ascending order in the Katkoyeh Formation, namely the Rossodus manitouensis/ Paltodus deltifer Concurrent Range Zone (Tremadocian, Lower Ordovician), the Juanognathus variabilis Range Zone (Floian, Lower Ordovician), and the Icriodella superba Range Zone (Katian–?Hirnantian, Upper Ordovician). The conodont biostratigraphy is discussed and analysed, improving the Ordovician intrabasinal correlation of Iran as well as correlation with distant palaeobiogeographic domains. The Upper Ordovician conodont assemblage is accompanied by two new species of ostracods: Satiellina zarandensis sp. nov. and Ceratopsis persicus sp. nov., both suggesting palaeobiogeographical affinities mainly with Gondwana and peri-Gondwanan regions.